Influence of C-reactive protein on the pharmacokinetics of voriconazole in relation to the CYP2C19 genotype: a population pharmacokinetics analysis - Ling, Jing; Yang, Xuping; Dong, Lulu; Jiang, Yan; Zou, Sulan; Hu, Nan (Frontiers in Pharmacology, 2024)
Voriconazole is a broad-spectrum triazole antifungal agent. A number of studies have revealed that the impact of C-reactive protein (CRP) on voriconazole pharmacokinetics was associated with the CYP2C19 phenotype. However, the combined effects of CYP2C19 genetic polymorphisms and inflammation on voriconazole pharmacokinetics have not been considered in previous population pharmacokinetics (PPK) studies, especially in the Chinese population. This study aimed to analyze the impact of inflammation on the pharmacokinetics of voriconazole in patients with different CYP2C19 genotypes and to optimize the dosage of administration. Data were obtained retrospectively from adult patients aged ≥ 16 years who received voriconazole for invasive fungal infections from October 2020 to June 2023. Plasma voriconazole was measured by high-performance liquid chromatography tandem mass spectrometry method. CYP2C19 genotyping was performed by the fluorescence in situ hybridization method. A PPK model was developed using the nonlinear mixed-effects models (NONMEM). The final model was validated using bootstrap, visual predictive check (VPC) and normalized prediction distribution errors (NPDE). Monte Carlo simulation was applied to evaluate and optimize the dosing regimens. A total of 232 voriconazole steady-state trough concentrations from 167 patients were included. A one-compartment model with first order and elimination adequately described the data. The typical clearance (CL) and the volume of distribution (V) of voriconazole were 3.83 L/h and 134 L, respectively. The bioavailability was 96.5%. Covariate analysis indicated that the CL of voriconazole was substantially influenced by age, albumin, gender, CRP and the CYP2C19 genetic variations. The V of voriconazole was significantly associated with body weight. An increase in the CRP concentration significantly decreased voriconazole CL in patients with CYP2C19 normal metabolizer (NM) and intermediate metabolizer (IM), but it had no significant effect on patients with CYP2C19 poor metabolizer (PM). Monte Carlo simulation based on CRP levels indicated that patients with high CRP concentrations required a decreased dose to attain the therapeutic trough concentration and avoid adverse drug reactions in NM and IM patients. These results indicate that CRP affects the pharmacokinetics of voriconazole and is associated with CYP2C19 phenotype. Clinicians dosing voriconazole should consider the patient's CRP level in CYP2C19 NM and IM patients.